Quantifying the potential impact of reducing recreational harvest limits on the catch of a key marine species using off-site angler survey data. (17th January 2023) - Ochwada-Doyle, Faith; Hughes, Julian; Fowler, Ashley M; Murphy, Jeffrey; Stark, Kate; Lowry, Michael; West, Laurie; Taylor, Matthew D
Abstract: Recreational fishing can have substantial ecological impacts, which must be managed against a background of critical socio-economic factors. However, it is often difficult to assess the effect of altered management arrangements on this sector's harvest. Recreational fishing surveys can assist in quantifying the impact of changes to harvest limits. Here, we use survey data collected in 2013/2014 and 2017/2018 to estimate the total catch of Dusky Flathead ( Platycephalus fuscus ), a key Australian marine species, under a daily harvest limit of 10 fish per angler and simulated scenarios where the limit is reduced to 5, 3, or 1 fish per angler. We then test the significance of these changes in harvest limit on catch and also model the potential effects of year and region using generalized linear mixed models (GLMMz). For both sampled time periods, the GLMMz found that only the most stringent harvest limit reduction to 1 fish per angler would lower retained harvest significantly. None of the reductions in harvest limit increased the number of released Dusky Flathead significantly. We discuss how this novel quantitative approach can be used to inform alternative output management regulations by taking into account their potential ecological and socio-economic benefits for a recreational fishery.